Elementy trzeciej kultury w przekładach polskich wersji Mistrza i Małgorzaty Michaiła Bułhakowa - Sadowska, Monika (Acta Polono-Ruthenica, 2018)
Nowadays the publishing market offers five Polish translations of Mikhail Bulgakov’s novel Master and Margarita, which appeared in the space of almost fifty years. The objective of the article is to concentrate on the way the components of third culture are rendered in the translations mentioned above. The author tries to draw the readers’ attention to the analogies and discrepancies within the translators’ choices. The analysis covers the names of natural phenomena, names of traditional culture phenomena, both material and spiritual, as well as the names of social and political life phenomena.